Transparency and government reputation: An experiment on signaling - Susana Otálvaro-Ramírez; Carlos G. Scartascini; Jorge M. Streb (Inter-American Development Bank (IDB), 2025)
Transparency initiatives are well-known tools to foster trust and empower citizens. To explain why some governments introduce them but others do not, we model these initiatives as a signal that complements the information provided by visible government performance and conduct a randomized survey experiment in the City of Buenos Aires, Argentina, where the incumbent mayor made a set of post-electoral promises. In a setting with relatively high trust priors, our results show that these initiatives matter in shaping citizens' perceptions of the reputation of the government. We find, however, strong heterogeneity among three groups of citizens. A group unfamiliar with the policy was impervious to treatment: they seem to react to deeds, not words, and have, on average, lower initial trust. The treatment effects are entirely through those vaguely familiar with the promises, closing the average gap in trust with those familiar with the promises. More generally, our study suggests that transparency initiatives may be an effective signal, though their informational value may be more limited than visible public performance.
Keywords: D72; D78; D82; D83; H41; 330; Rent-seeking; Promises; Signaling; Social learning; Trust; Reputation; Politicaleconomy; Development; Survey experiment